Risk Factors for Poststroke Depression: An Integrative Review. Issue 2 (April 2017) - Babkair, Lisa A.
Abstract : ABSTRACT: Background: Poststroke depression (PSD) is the most common stroke-related emotional disorder and affecting one-third of stroke survivors at any time up to 5 years after stroke. Poststroke depression affects rehabilitation after stroke and may delay recovery. The purpose of this integrative review is to analyze the state of the science in regard to risk factors for PSD.Methods: The electronic databases PubMed, Cumulative Index to Nursing and Allied Health Literature, and PsycInfo were searched. Inclusion criteria included (1) peer-reviewed primary observational Western studies, (2) PSD as the primary outcome, (3) included adult stroke survivors, and (4) and published after 2004. The integrative review guidelines were used for analysis.Results: From an original of 406 articles identified, 18 met the inclusion criteria and were reviewed: 3 cross-sectional, 14 prospective cohort, and 1 case control. The most common risk factors associated with PSD are stroke severity, cognitive impairment, physical disability, and functional dependency. Others factors including demographic and social factors and medical history were not consistent across studies.Conclusions: Overall, quality of the research was limited by small sample sizes, selection bias, number of selected variables, and lack of multivariate analyses. Nurses should identify patients at risk for PSD through early depression screening and provide interventions to enhance rehabilitation and improve recovery.